Interview with Peter Greenaway1, the Filmmaker and Multimedia-Artist - Baez Meza, Marcelo (Revista Criterios, 2011)
Provocative and inconsiderate, the British artist and cinema director Peter Greenaway speaks plainly with the author of this interview about his thinking related to the Cinema, Literature and Painting. His works in general are full of pictorial references; they are based on the Dutch painter Johannes Vermeer. In the same way he has been influenced by Wilson, Constable, Gainsborough, Turner and Palmer. He attributes his academic training to the world of the Fine Arts. Without regard he says that all filmmakers are ignorant, that the film should no longer be a slave of the literature, but the reality is different and it must be accepted and it is necessary to update the language of the cinema using the new technology. Regarding his paintings, he defines himself as a selfish person, since he tries not to sell any. His movies are based on his paintings, and these last ones with his world view.